2015
DOI: 10.1016/j.neuroimage.2015.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Functional resting-state connectivity of the human motor network: Differences between right- and left-handers

Abstract: Handedness is associated with differences in activation levels in various motor tasks performed with the dominant or non-dominant hand. Here we tested whether handedness is reflected in the functional architecture of the motor system even in the absence of an overt motor task. Using resting-state functional magnetic resonance imaging we investigated 18 right- and 18 left-handers. Whole-brain functional connectivity maps of the primary motor cortex (M1), supplementary motor area (SMA), dorsolateral premotor cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 58 publications
2
36
1
Order By: Relevance
“…In theory, one might explain this discrepancy of results by arguing that handedness as a sensorimotor phenomenon, instead of language lateralization, determines the mean AFC matrix, and thus AFC-scores. We believe this to be highly unlikely, however, considering that all correlations between LTL-score, handedness, and AFC-score were significantly positive, and that asymmetries were not overrepresented in connections with motor areas as would be predicted based on the fact that hand preference can be decoded from RS correlations between the different motor areas (Pool et al 2015). We have as yet no explanation for the apparent contradiction in results.…”
Section: Discussionmentioning
confidence: 74%
“…In theory, one might explain this discrepancy of results by arguing that handedness as a sensorimotor phenomenon, instead of language lateralization, determines the mean AFC matrix, and thus AFC-scores. We believe this to be highly unlikely, however, considering that all correlations between LTL-score, handedness, and AFC-score were significantly positive, and that asymmetries were not overrepresented in connections with motor areas as would be predicted based on the fact that hand preference can be decoded from RS correlations between the different motor areas (Pool et al 2015). We have as yet no explanation for the apparent contradiction in results.…”
Section: Discussionmentioning
confidence: 74%
“…A reflection of how strongly a person prefers one hand, degree of hand preference is a behavioural reflection of cerebral lateralization for handedness. This has been reported in several studies assessing both structural and functional cortical organization [30, 31, 32]. For example, using resting-state fMRI, Pool et al [32] identified stronger interhemispheric functional connectivity in right handers.…”
Section: Introductionmentioning
confidence: 56%
“…This has been reported in several studies assessing both structural and functional cortical organization [30, 31, 32]. For example, using resting-state fMRI, Pool et al [32] identified stronger interhemispheric functional connectivity in right handers. As such, the authors suggested functional connectivity between left primary motor cortex and right dorsolateral premotor cortex may be used as an indicator of handedness [32].…”
Section: Introductionmentioning
confidence: 56%
“…Typically, right-handed individuals show stronger resting state functional connectivity in the left hemisphere, compared to that of left-handed individuals (Saenger, Barrios, Martínez-Gudiño, & Alcauter, 2012). Greater left-sided functional connectivity has been shown to be associated with better cognitive (e.g., reading, comprehension) (Koyama et al, 2011) and motor performance (e.g., hand movements) (Barber et al, 2011; Pool, Rehme, Eickhoff, Fink, & Grefkes, 2015; Pool, Rehme, Fink, Eickhoff, & Grefkes, 2014). O'Muircheartaigh et al (2013) reported that greater leftward asymmetry of myelin content in caudate and anterior frontal cortex was associated with better receptive language skills in healthy children between 1 to 6 years.…”
Section: Discussionmentioning
confidence: 99%